The ins and outs of the evolutionary origin of teeth. Issue 1 (15th September 2014) - Donoghue, Philip C. J.; Rücklin, Martin
SUMMARY: The role of teeth and jaws, as innovations that underpinned the evolutionary success of living jawed vertebrates, is well understood, but their evolutionary origins are less clear. The origin of teeth, in particular, is mired in controversy with competing hypotheses advocating their origin in external dermal denticles ("outside‐in") versus a de novo independent origin ("inside‐out"). No evidence has ever been presented demonstrating materially the traditional "outside‐in" theory of teeth evolving from dermal denticles, besides circumstantial evidence of a commonality of structure and organogenesis, and phylogenetic evidence that dermal denticles appear earlier in vertebrate phylogeny that do teeth. Meanwhile, evidence has mounted in support of "inside‐out" theory, through developmental studies that have indicated that endoderm is required for tooth development, and fossil studies that have shown that tooth‐like structures evolved before dermal denticles (conodont dental elements), that tooth replacement evolving before teeth (thelodont pharyngeal denticles), and that teeth evolved many times independently through co‐option of such structures. However, the foundations of "inside‐out" theory have been undermined fatally by critical reanalysis of the evidence on which it was based. Specifically, it has been shown that teeth develop from dermal, endodermal or mixed epithelia and, therefore, developmental distinctions between teeth and dermal denticles are diminished. Furthermore the odontode‐like structure of conodont elements has been shown to have evolved independently of dermal and internal odontodes. The tooth‐like replacement encountered in thelodont pharyngeal odontodes has been shown to have evolved independently of teeth and tooth replacement and teeth have been shown to have evolved late within the gnathostome stem lineage indicating that it is probable, if not definitive, that teeth evolved just once in gnathostome evolution. Thus, the "inside‐out" hypothesis must be rejected. The phylogenetic distribution of teeth and dermal denticles shows that these odontodes were expressed first in the dermal skeleton, but their topological distribution extended internally in association with oral, nasal and pharyngeal orifices, in a number of distinct evolutionary lineages. This suggests that teeth and oral and pharyngeal denticles emerged phylogenetically through extension of odontogenic competence from the external dermis to internal epithelia. Ultimately, internal and external odontodes appear to be distinct developmental modules in living jawed vertebrates, however, the evidence suggests that this distinction was not established until the evolution of jawed vertebrates, not merely gnathostomes.